PROTEST: THE LANGUAGE OF PROFECY - Susaimanickam, J (Journal of Dharma, 2001)
In their quest and struggle for identity, dignity and full humanity, the dalits. have changed the rigidity and legistimacy of the caste system, and their leaders have championed their cause by striking a path of dissent through counter-culrural movements and literature’. The Dalit Sahitya (literature) Movement, which was started in Maharashtra, aimed at the liberation of the dalits through social change, striking a violent note of protest against the legistimacy of the caste system’ and against the organized violence savagely lashed out on them in God’s name.